Babylonian House Numbers and Squares of Zodiacal Signs: The Origin of the Quadruplicities, Part II - Brack-Bernsen, Lis (Aestimatio, 2022)
The texts BM 36628+ and BM 45720 contain number schemes, which in their first four columns list consecutive lines of Calendar Texts. These texts add six more columns (columns 5–10) to the classic Calendar Text. Therefore, we shall call them expanded Calendar Texts. The additional column 10 lists house numbers j, while column 9 contains four signs (labeled i) over four consecutive lines, one of which equals a j-value. As we shall see, the i-values are chosen so that they always form the zodiacal squares with j as one of the corners. I investigate the system behind the schemes by analyzing their number columns. We thus find a structure similar to that of the circular tablet BM 47762, which I presented in Part I [Aestimatio ns 2.2 (2021) 43–58]. This tablet lists the dates of first half, full, second half, and black Moon, where the zodiacal position of these special lunar phases joins to a square in the zodiacal circle. I investigate the connection between the two systems.